Edukasi dan Demonstrasi Penanganan C-Spine Control pada Korban Gawat Darurat dalam Kondisi Out of Hospital - Rosyadi, IMRON; Susilawati, Desi; Elesee, Vice (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2026)
Emergency conditions in the school environment have a significant prevalence in community emergency incidents. This community service aims to increase the knowledge and skills of students at SMKN 4 Kota Bengkulu in handling emergencies, especially C-Spine Control. The community group that partners in this community service activity is SMKN 4 Kota Bengkulu. Community service is carried out in 3 stages: preparation stage, implementation stage, and evaluation stage. Participants will undergo a pretest to assess their skill scores. After that, the community service team will teach and demonstrate C-Spine Control handling. The team will then reevaluate to measure skill scores. The results show an improvement in the skill scores of students at SMKN 4 Kota Bengkulu after receiving emergency handling demonstrations. The school can create a regular schedule to hone and refresh students' abilities in providing emergency care, especially in emergencies in the school environment.